A nonlocal strain gradient theory for dynamic modeling of a rotary thermo piezo electrically actuated nano FG circular plate. (15th January 2019) - Mahinzare, Mohammad; Jannat Alipour, Mehdi; Sadatsakkak, Seyed Abbas; Ghadiri, Majid
Highlights: Vibrational behavior of FGPM in a nano circular plate subjected to rotational and thermal loads is studied. The governing equations of FGPM nano circular plate obtained and solved using the differential quadrature method (DQM). Vibrational behavior of FGPM nano circular plate is affected by temperature rises, angular velocity, external voltage, FG power index, nonlocal parameter and material length scale. Abstract: In this paper, vibrational behavior of functionally graded piezoelectric material (FGPM) in a nano circular plate subjected to rotational and thermal loads is studied. Thermo-electro–elastic characteristics of FGPM nano circular plate are changed continuously along the thickness with the power-law model. This analysis is based on nonlocal strain gradient theory (NSGT), strain gradient theory (SGT) and nonlocal Eringen theory (NET) within the first order shear deformation theory (FSDT). Via Hamilton's principle, the governing equations of FGPM nano circular plate obtained and solved using the differential quadrature method (DQM). It is seen that the vibrational behavior of FGPM nano circular plate is considerably affected by temperature rises, angular velocity, external voltage, FG power index, nonlocal parameter and material length scale for clamped and hinged boundary conditions.